GhERF41, a group IIIe ERF protein, participates in regulating cell wall synthesis in cotton fiber - Gao, Yanan; Cui, Yuke; Li, Shuaijie; Feng, Mengru; Liu, Le; Xu, Wenliang; Zhang, Jie (Industrial crops and products, 2023)
Cotton provides the world’s leading natural fiber. Cotton fiber cell wall dictates pivotal fiber quality indexes such as fiber length and strength, in addition to defining fiber cell morphology. However, the regulatory mechanism underpinning cotton fiber cell wall biosynthesis remain hitherto elusive. Here, an ERF IIIe subfamily gene, GhERF41, was identified and characterized. Expression of GhERF41 in Arabidopsis resulted in dwarf plants and thinner inflorescence stems. Further staining of stem cross sections showed that expressing GhERF41 contributed to thickened cell wall of fiber cells and ectopic primary cell wall (PCW) deposition, which is in line with the conspicuous alterations in the expression of many PCW and secondary cell wall (SCW) genes. Moreover, GhERF41 can partially rescue the phenotype of nst1nst3 double mutant that is defective in SCW deposition in fiber cells by inducing more PCW deposition in the stem. Finally, genetic downregulation of GhERF41 in cotton led to shorter mature fibers and reduced crystalline cellulose content. Dual-luciferase assay demonstrated that GhERF41 could activate both the PCW-associated GhCesA1–2 and the SCW-associated GhCesA4–2 transcriptions. Overall, our results showed that GhERF41 has the potential to regulate PCW and SCW synthesis yielding new insights into the regulatory mechanisms underpinning cotton fiber development and providing a novel target gene to coordinate fiber length and strength. •GhERF41 plays an important role in fiber development.•GhERF41 differentially regulates primary and secondary cell wall formation.•GhERF41 function by binding to the promotes of cellulose synthase genes.